PENGARUH LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA PT ARWANA CITRAMULIA TBK - Amanah, Hafidatul; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to empirically examine the effect of liquidity, profitability, and solvency on the financial performance of PT Arwana Citramulia Tbk over a ten-year observation period from 2016 to 2025. This research adopts a quantitative method with an associative causal approach, aiming to analyze the relationship and causal effect among variables. The data used in this study are secondary data derived from the company’s annual financial statements. Liquidity is measured using the Current Ratio (CR), profitability is proxied by Return on Assets (ROA), solvency is measured using the Debt to Equity Ratio (DER), and financial performance is represented by Return on Equity (ROE). The analytical technique employed is multiple linear regression analysis, supported by classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results of this study indicate that profitability has a positive and statistically significant effect on financial performance. Meanwhile, liquidity does not show a statistically significant effect, and solvency demonstrates a negative relationship with financial performance. Simultaneously, liquidity, profitability, and solvency collectively exert a significant influence on financial performance. These findings provide important implications for financial decision-making and investment evaluation.